Integrated enviromantal modeling : - Ramaswami, Anu (John Wiley & Sons, 2005)
A unified presentation of environmental model development, implementation, and testing. Integrated Environmental Modeling teaches model development, model implementation, and model testing skills in a unified manner, crosscutting the three "media" comprising environmental systems—air, water, and soil—by focusing on parallels and similarities between them, and introducing a new generation of multimedia models. No other single volume offers comprehensive coverage of chemical transport and fate in all three environmental media, including the resulting impacts on the biosphere and human health, with a focus on the fundamental processes underlying environmental modeling. Integrated Environmental Modeling provides broad-based training in the development of pollutant transport and fate models in air, water, and soil, with a focus on five essential competencies